Effect of particulate size on mechanical strength of Anadara granosa bioceramic - Nur Farahiyah, Mohammad; Kanesvaran, Ghirubaagiri; Siti Marhainis, Othman; Intan Shafinaz, Mohammad (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/